2018
DOI: 10.1097/cej.0000000000000397
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal cancer and markers of anemia

Abstract: Unexplained iron-deficiency anemia is an important marker for colorectal cancer (CRC). Our objectives were as follows: (a) to assess whether the association between anemia and CRC can be detected on the 'Clinical Practice Research Datalink', (b) to evaluate the timing between laboratory changes and CRC detection, and (c) to analyze its association with survival. We conducted a case-control study on patients with an incident CRC diagnosis during 2008-2012 and a 1 : 1-matched control group. We compared anemia ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 30 publications
2
12
0
Order By: Relevance
“…Our group previously reported that MCV was a prognostic factor for RFS in patients who underwent R0 resection for stage I/II/III CRC, independent of the tumor stage [22]; a low MCV or microcytosis (MCV < 80 fL) was associated with favorable outcomes. Schneider C et al reported that Hb and MCV dropped shortly before the CRC diagnosis, and low MCV was weakly associated with survival of patients with CRC [23]. CRC is often accompanied by iron-deficiency anemia, which leads to decreased MCV.…”
Section: Discussionmentioning
confidence: 99%
“…Our group previously reported that MCV was a prognostic factor for RFS in patients who underwent R0 resection for stage I/II/III CRC, independent of the tumor stage [22]; a low MCV or microcytosis (MCV < 80 fL) was associated with favorable outcomes. Schneider C et al reported that Hb and MCV dropped shortly before the CRC diagnosis, and low MCV was weakly associated with survival of patients with CRC [23]. CRC is often accompanied by iron-deficiency anemia, which leads to decreased MCV.…”
Section: Discussionmentioning
confidence: 99%
“…Even though possible positive correlations between levels of Ferritin and cancer-specific processes (including CRC) have been shown, iron deficiency anemia caused by chronic gastrointestinal bleeding might antagonize this effect. 41,42 The progression in colorectal neoplasia from HRA to CRC might cause increased gastrointestinal bleeding, which could explain why levels of Ferritin are decreased in individuals with CRC compared to individuals with HRA in the present study.…”
Section: Discussionmentioning
confidence: 73%
“… Complex interactions; levels in the circulation are positive correlated to cancer-specific processes which could be antagonized by iron-deficiency anemia caused by chronic gastrointestinal bleeding. [ 26 , 27 , 37 , 41 , 42 ] Galectin-3 Increased expression in tumor tissue of CRC and associated with advanced CRC. [ 43 ] hs-CRP Associated with CRC and carcinogenesis in general.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, preoperative CRP/MCV could predict aggressive tumor biology (39), which is conducive to risk stratification and guiding clinical work. Indeed, estimation of changes in CRP reflects the presence and intensity of an inflammatory process and differentiates inflammatory from non-inflammatory conditions, which are useful in managing the patient's disease and predicting the prognostic value in certain diseases (40). It has been reported that anemia in CRC frequently shows a microcytic phenotype (39,41), especially in high-grade T stage, proximal colon tumor location, lymph node metastasis, and elevated serum CRP with or without hypoalbuminemia (14,27).…”
Section: Discussionmentioning
confidence: 99%
“…Second, several diseases, such as iron deficiency anemia, alpha or beta-thalassemia minor, and liver disease, which can affect the value of MCV, were not screened; this may have led to a selection bias. Third, the use of a single parameter to assess nutritional status has been questioned since many other nutritional factors affect outcomes (40). Lastly, this study was conducted over a long period between 2004 and 2019, which can be associated with historical biases in treatment strategy and perioperative management.…”
Section: Discussionmentioning
confidence: 99%